On the method of determination of level of social activity of veterans in provinces of the Roman Empire (the case of Lower Moesia) - Martemyanov, Alexei (Studia Europaea Gnesnensia, 2017)
Active involvement of army veterans in local governance and religious life of provincial towns and villages of the Roman Empire is generally determined as the ratio of number of retired soldiers who were magistrates and priests to the total number of veterans, known from all the inscriptions found on the territory of a province. In the opinion of the author, this approach may lead to a misperception of this aspect of the former soldiers’ life and consequently needs to be revised. This paper presents an alternative method of resolving the problem and outlines perspectives for its practical application on the example of material relating to the province of Lower Moesia.